2020
DOI: 10.1039/d0py00755b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of synthesized cyclic and linear cationic copolymers

Abstract: Cationic polymers are one of the main classes of materials investigated against bacteria through the membrane-lysis mechanism. The cationic-hydrophobic balance and distribution of cationic and hydrophobic moieties of these polymers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Xu et al investigated cationic polymers as the main classes of materials against bacteria through the membrane-lysis mechanism. They studied antibacterial effects of linear and cyclic monomers of cyclic poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) based copolymers with various components by the intra-chain click cyclization of α-alkyne-ω-azido via atom transfer radical polymerization [ 23 ]. In another study of amphiphilic polymers of thiazole ring 2-(2-(4-methylthiazol-5-yl)ethoxy)carbonyl)oxy)ethyl methacrylate monomer (MTZ) and non-hemotoxic poly(ethylene glycol) side chains (poly(ethylene glycol) methyl ether methacrylate (PEGMA) observed that longer hydrophobic chain, octyl were much more hemotoxic than their corresponding butylated copolymers [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al investigated cationic polymers as the main classes of materials against bacteria through the membrane-lysis mechanism. They studied antibacterial effects of linear and cyclic monomers of cyclic poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) based copolymers with various components by the intra-chain click cyclization of α-alkyne-ω-azido via atom transfer radical polymerization [ 23 ]. In another study of amphiphilic polymers of thiazole ring 2-(2-(4-methylthiazol-5-yl)ethoxy)carbonyl)oxy)ethyl methacrylate monomer (MTZ) and non-hemotoxic poly(ethylene glycol) side chains (poly(ethylene glycol) methyl ether methacrylate (PEGMA) observed that longer hydrophobic chain, octyl were much more hemotoxic than their corresponding butylated copolymers [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…After incubation at 37 °C for 1 h, the bacterial cells were fixed with GA (2.5%) solution at room temperature for 30 min. The cells were washed with fresh PBS three times to remove the residual GA solution and dehydrated using a series of graded ethanol (30,50,70,90, and 100 vol.%) aqueous solutions. The dehydrated cells were dried at room temperature for 24 h, and their morphology was examined using field emission scanning electron microscopy (FE-SEM, S-4800, Hitachi).…”
Section: Microscopic Studiesmentioning
confidence: 99%
“…Importantly, despite its similar M w , S-QAR had smaller D h than L-QAR, which could be attributed to its compact and globular molecular architecture resulting from multiple linear arms constrained on the core. [48][49][50] Particularly, D h of S-QAD was much smaller than that of L-QAD because its compact and constrained chain structure could effectively suppress its intermolecular entanglement and interactions, thereby reducing its aggregation. 51,52 Notably, S-QAC had D h ∼3.5 times larger than its diameter measured by TEM (Fig.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular interest to PDMAEMA-based gels is driven by their antibacterial activity [ 65 ] and applications as non-viral gene delivery systems [ 66 , 67 ]. Although PDMAEMA is a polymer with relatively high cytotoxicity [ 68 , 69 ], toxicity of PDMAEMA gels is strongly reduced by copolymerization of DMAEMA monomers with biocompatible monomers [ 70 , 71 , 72 , 73 ].…”
Section: Fitting Of Experimental Datamentioning
confidence: 99%